ПОЛИТИЧЕСКАЯ ЭКСТРАВАГАНЦА КАК ДРАМАТИЧЕСКИЙ ЖАНР (на материале пьес Бернарда Шоу) - Sokolyansky, Mark (Zagadnienia Rodzajów Literackich, 2022)
The paper deals with the semantic and structural specificity of political extravaganza as a genre of dramaturgy. The history of this literary and dramatic kind and also its scantily explored genetic connection with the dramatic pamphlet, which arose in the 18th-century English theatre, are briefly retraced. Its artistic peculiarity is investigated by using material from several plays of Bernard Shaw, which were written from the 1920s–1930s (The Apple Cart, Too True to be Good, Geneva, On the Rocks). The genre definition was used by the playwright for the first time as a subtitle to the play The Apple Cart, the first performance of it took place in Warsaw in 1929; the extravaganza was staged by Arnold Szyfman at the “Teatr Polski”. Special attention is paid in the article to such features of political extravaganza, as paradox, the grotesque and eccentricity, which become apparent at some levels of dramatic text: in the linguo-stylistic originality of the tirades and dialogues, as well as in the extensive stage directions and sometimes in the titles, in the characters of personages, in construction of the plots and in the composition of the plays. Of primary interest is also the eccentric treatment of the artistic time in the plays based on the historical personalities or episodes, and in the introduction of fantastical elements to the dramatic action. The essential role of the concentrated eccentricity in the sharpening and the emphasized topicalization of political satire is also discussed in the paper.